Unraveling fetal venous disorders: An integrated approach in fetal echocardiography and their clinical significance - Wei-Hsiang Tseng; Hsi-Chu Lai; Li-Ling Lin; Shen-Ling Jan; Hsien-Wen Peng; Jenn-Jhy Tseng (Elsevier, 2024)
Objective: Fetal venous system malformations frequently coincide with cardiac or extracardiac anomalies. This study explores our experience with an integrated fetal echocardiography approach and analyzes the characteristics and outcomes of fetal venous system disorders. Materials and methods: We conducted a retrospective study with 7048 pregnant women (7255 fetuses) who underwent complete two-dimensional (2D) fetal echocardiographic examinations. We primarily employed an integrated 2D approach. Three-/four-dimensional (3D/4D) spatiotemporal image correlation was supplemental. Fetal venous disorders were classified into 3 groups: cardinal (Group 1), umbilical and vitelline (Group 2), and pulmonary (Group 3) systems, based on embryological-anatomical considerations. Maternofetal data were recorded alongside imaging diagnoses. Results: Congenital venous malformations were identified in 98 fetuses, yielding a prevalence of 1.35% (98/7255). Six participants had coexisting venous disorders from different groups. Group 1 included 48 fetuses with persistent left superior vena cava (LSVC) and 3 others (unidentified brachiocephalic vein, left inferior vena cava (IVC), and interrupted IVC with azygous continuation to SVC). Group 2 had 39 fetuses with persistent right umbilical vein and 7 with umbilical-portal-ductus venosus disorders. Group 3 had 7 fetuses with pulmonary venous return disorders. Group 2 showed the most favorable outcomes (alive and without neonatal death), while Group 3 exhibited the poorest. Associated cardiac defects were observed in 43.1% of Group 1, 8.7% of Group 2, and 57.1% of Group 3 (P < 0.001), displaying a broad spectrum of non-specific anomalies. Meanwhile, Group 2 had a greater occurrence of a single venous disorder (93.5%) compared to Group 1 (88.2%) and Group 3 (57.1%) (P = 0.020). Conclusion: Our approach offers an integrated strategy for assessing the fetal venous system during fetal echocardiography, providing multiple views to characterize venous anomalies. The presence of a fetal venous disorder may indicate the coexistence of more severe abnormalities, and the prognosis depends on associated anomalies or the venous disorders per se.